A case of orbital apex syndrome due to Pseudomonas aeruginosa infection - Takeshi Kusunoki; Kaori Kase; Katsuhisa Ikeda (Clinics and Practice, 2011)
Orbital apex syndrome is commonly been thought to have a poor prognosis. Many cases of this syndrome have been reported to be caused by paranasal sinus mycosis. We encountered a very rare case (60-year-old woman) of sinusitis with orbital apex syndrome due to Pseudomonas aeruginosa infection. She had received insulin and dialysis for diabtes and diabetic nephropathy, moreover anticoagulants after heart by-pass surgery. She underwent endoscopic sinus operation and was treated with antibiotics, but her loss of left vision did not improve. Recently, sinusitis cases due to Pseudomonas aeruginosa were reported to be a increasing. Therefore, we should consider the possibility of Pseudomonas aeruginosa as well as mycosis as infections of the sinus, especially inpatients who are immunocompromised body.